Biocompatibility of variable thicknesses of a novel directly printed aligner in orthodontics - Maximilian Bleilöb; Claudia Welte-Jzyk; Vanessa Knode; Björn Ludwig; Christina Erbe (Scientific Reports)
Abstract Direct printed aligners (DPAs) offer benefits like the ability to vary layer thickness within a single DPA and to 3D print custom-made removable orthodontic appliances. The biocompatibility of appliances made from Tera Harz TA-28 (Graphy Inc., Seoul, South Korea) depends on strict adherence to a standardized production and post-production protocol, including UV curing. Our aim was to evaluate whether design modifications that increase layer thickness require a longer UV curing time to ensure biocompatibility. Specimens with varying layer thickness were printed to high accuracy using Tera Harz TA-28 and the Asiga MAX 3D printer (Asiga SPS ™ technology, Sydney, Australia). UV curing durations were set at 20, 30 and 60 min. Cytotoxicity was evaluated using the AlamarBlue assay on human gingival fibroblasts. Cell viability decreased with increasing specimen thickness (significant for 2 mm [p < 0.001], 4 mm [p < 0.0001], and 6 mm [p < 0.01]) under the manufacturer-recommended 20-min UV curing. Extending the curing time did not improve cell viability. However, cell viability never decreased by more than 30%, meeting EN ISO 10993-5 standards for non-cytotoxicity. The standard 20-minute UV curing protocol ensures the biocompatibility and patient safety of Tera Harz TA-28 for material thicknesses up to 6 mm.